The aftermath of Employee Redundancy in Zimbabwean Entrepreneurial organizations - Mabwe, Notion (IJRDO - Journal of Social Science and Humanities Research, 2017)
The current adverse economic situation in Zimbabwe, which has been persistent, has driven many companies out of their business. The surviving companies are however forced to restructure their operations. The on-going economic trend opened a paradigm shift that gave an opportunity to employee redundancy in Zimbabwean organizations. This study attempt to assess the aftermath of employee redundancy focusing on the entrepreneurial business in Masvingo, Retail supermarket, Clothing factory, Insurance and Transport. A research was conducted using questionnaires and face-to-face interview. Fifty employees who are conversant with this phenomenon were purposively drawn from entrepreneurial business organizations from Masvingo suburban area. Findings of the study revealed that capitalization of entrepreneurial business should be a priority number one in-order to minimize employee redundancy